Medical Undergraduate Students’ Viewpoint on Online Learning During COVID-19 Pandemic - Rathoria, Ekansh; Richa Rathoria; Singal, Umang; Singh, Asheesh Pratap; Bansal, Utkarsh; Agrawal, Prashant (Journal of Nepal Paediatric Society, 2022)
Introduction: The coronavirus pandemic constrained medical colleges to discontinue face-to-face learning activities and suddenly switch to an online learning model. Technology is making its way into medical education, also being advocated by the medical commission, though students’ perception is still poorly understood. This study aimed to investigate the medical students’ perspectives on online learning. Methods: It was a cross-sectional, questionnaire-based study to assess the demographics, merits, demerits, recommendations, and suggestions for online learning by medical undergraduates. A combination of multiplechoice, Likert scale-based, and open-ended questions was used. Results: The student-perceived merits of e-learning were flexibility in timings, convenience, self-directed learning approach, and prevention of pandemic spread. The demerits viewed were lack of personal interaction with teacher and batchmates, increased distractions, lack of high-speed internet, and less / no hands-on experience. The classroom teaching was the favoured teaching method (45.7%) and easy to comprehend (55.8%). The recommendations included: medical curriculum should not be completely e-learning based (84.1%), training for using online applications (51.4%), providing high-speed internet and apps with no time limit (83.7%), taking online tests (64.4%), student’s feedback (75%), and frequent online demonstrations and simulations (64.9%). Overall, 52.4% of students’ morale was positive towards e-learning. Students rated blended teaching as the preferred teaching method. Conclusions: Medical students still prefer face-to-face learning and opted for blended learning over complete e-learning. Appropriate steps like training faculties, providing high-speed internet, taking formative tests, giving online demonstrations, involving simulations, and student feedback can improve e-learning quality.